Elevated Plasma Levels of MMP-12 Are Associated With Atherosclerotic Burden and Symptomatic Cardiovascular Disease in Subjects With Type 2 Diabetes. Issue 7 (July 2015) - Goncalves, Isabel; Bengtsson, Eva; Colhoun, Helen M.; Shore, Angela C.; Palombo, Carlo; Natali, Andrea; Edsfeldt, Andreas; Dunér, Pontus; Fredrikson, Gunilla Nordin; Björkbacka, Harry; Östling, Gerd; Aizawa, Kunihiko; et al.
Abstract : Objective—: Matrix metalloproteinases (MMPs) degrade extracellular matrix proteins and play important roles in development and tissue repair. They have also been shown to have both protective and pathogenic effects in atherosclerosis, and experimental studies have suggested that MMP-12 contributes to plaque growth and destabilization. The objective of this study was to investigate the associations between circulating MMPs, atherosclerosis burden, and incidence of cardiovascular disease with a particular focus on type 2 diabetes mellitus. Approach and Results—: Plasma levels of MMP-1, -3, -7, -10, and -12 were analyzed by the Proximity Extension Assay technology in 1500 subjects participating in the SUMMIT (surrogate markers for micro- and macrovascular hard end points for innovative diabetes tools) study, 384 incident coronary cases, and 409 matched controls in the Malmö Diet and Cancer study and in 205 carotid endarterectomy patients. Plasma MMP-7 and -12 were higher in subjects with type 2 diabetes mellitus, increased with age and impaired renal function, and was independently associated with prevalent cardiovascular disease, atherosclerotic burden (as assessed by carotid intima-media thickness and ankle-brachial pressure index), arterial stiffness, and plaque inflammation. Baseline MMP-7 and -12 levels were increased in Malmö Diet and Cancer subjects who had a coronary event during follow-up. Conclusions—: The plasma level of MMP-7 and -12 are elevated in type 2 diabetes mellitus, associated with more severe atherosclerosis and an increased incidence of coronary events. These observations provide clinical support to previous experimental studies, demonstrating a role for these MMPs in plaque development, and suggest that they are potential biomarkers of atherosclerosis burden and cardiovascular disease risk. Abstract : Supplemental Digital Content is available in the text.